Assessment and classification of hazardous street trees in University of Ibadan Nigeria (2010)
The study was carried out to assessed and classified hazardous trees within the University of Ibadan (UI) campus, Oyo State, Nigeria. The study population was 25 municipal tree species comprising of 420 individual trees located along the major roads of the study area, which were considered hazardous to the community. With the aids of data form, health assessments which include a review of defects, surrounding site conditions, and potential targets were carried out. Data collected were subjected to statistic analysis. The result revealed that 31.42% of the total tree species samp1ed within the study area are samena senna. Hazardous trees were generally lower along Agriculture, Masaba and Veterinary roads and they are 0.47%, 0.95% and 1.66% respectively. Oduduwa road had highest number of poor-quality tree with multiple defects (22.38%). A total of 132 species of samena senna bad extremely high probability of failure while the probability of 69 species of Delonix regia to strike a target is extremely high, this species have very shallow roots and the species is easily affected by root/stem rots resulting in heavy damages even with little storm. Ten species of Samena senna affect the road, 33 species of Gliricidia sepium affect the walkway, 60 species of Delonix regia affect the building, 71 species of Samena senna cause street light obstruction and 6 species of Samena senna are affecting the underground cable. In conclusion the study revealed that all the sampled municipal trees of university of Ibadan were defective having some negative impacts for infrastructure damages (e.g damage to building and sidewalks). Since there will always be a common Interaction among people, property and trees in the University community, detection and removal of trees that are likely to be hazardous is essential.